Impact of Arbuscular mycorrhizal fungi on growth of banana genotypes in three different, pasteurized and non-pasteurized soils of Rwanda - Gaidashova, S.V.; Nsabimana, A.; Asten, Piet J.A. van; Delvaux, B.; Elsen, A.; Declerck, S. (CAB International, 2013)
Arbuscular mycorrhizal (AM) fungi are known to improve the growth of many crops of agricultural importance. The amplitude of this growth improvement may vary depending on soil type. Here, we report the effect of the application of indigenous AM fungi, isolated from a Nitisol from Kirehe (eastern Rwanda), on the growth and root characteristics of three banana (Musa spp.) genotypes: 'FHIA-l7' (AAAA), 'Musakala' (AAA-EA) and 'Sukali Ndiizi' (AAB), grown in pasteurized and non-pasteurized Acrisol, Ferralsol or Nitisol. Root characteristics differed significantly between soil types (P < 0.001) and banana genotypes (P < 0.05). The poorest root development was observed on the Acrisol and the best on the Nitisol, irrespective of genotype. 'Musakala' had a smaller root system than 'FHLA-l7' and '5ukali Ndiizi', Inoculation resulted in highly significant (P < 0.001) differences in frequency of root colonization between soil types in all genotypes and treatments, with the highest frequency observed in the Nitisol and Ferralsol and the lowest in the AcrisoL Inoculation increased plant growth and dry weight (P < 0.05) but the effect was tess marked in nonpasteurized treatments than in pasteurized treatments in all soils and genotypes. The exception was the Ferralsol, where pasteurization did not result in a significant increase in plant growth. The highest relative plant growth increase caused by AM fungi v.ras observed in the AcrisoL This was observed for all genotypes and treatments and could possibly be linked to the greater limitations to root growth in this soil type. Poorer root development of 'Musakala' coincided with its highest response to the AM fungi inoculation compared with other genotypes, which suggested its higher AM fungal dependency.